Empowering Women Fish Farmers through Technology Transfer for Diversification of Catfish and Local Cempedak Products - Mery Sukmiwati; Tjipto Leksono; Dian Iriani; Henni Syawal; Morina Riauwaty; Efawani; Nofri Sandria; Suparmi Suparmi; Indah Prasetya Putri (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: Rural fisheries communities often face limited value addition due to inadequate processing technology, weak food safety practices, and low entrepreneurial capacity. In Kuok Village, Kampar Regency, abundant catfish (Pangasius sp.) and local forest cempedak remain underutilized as innovative food products. Purpose of the Study: The community service program on technology transfer of fish-based food processing was carried out in Kuok Village, Kampar Regency, focusing on the utilization of catfish (Pangasius sp.) and local forest cempedak as potential raw materials for innovative food products. Methods: Activities were conducted in three stages: (1) training on GMP, CPPB-IRT, entrepreneurship, and marketing; (2) hands-on production of Cemfish dimsum, cookies, and fresh noodles; and (3) provision of appropriate processing equipment to support sustainable production and quality improvement. Results: The results showed that participants acquired new skills in hygienic production, product diversification, and business management. Moreover, the program empowered women through active participation in fisheries-based entrepreneurship, strengthening household income and promoting sustainable local food businesses. This activity demonstrates that technology transfer combined with capacity building in management and marketing can create distinctive, competitive, and marketable village-based products, while also reinforcing local identity.